Physiological and immunological responses of Nile tilapia fed dietary supplementation of sweet basil ethanolic and aqueous extracts - Mansour, Abdallah Tageldein; Diab, Amany M.; Khalil, Riad H.; Eldessouki, Elsayed A.; El-Sabbagh, Nasser; Elsamannoudy, Salma I.; Younis, Nehal A. (Frontiers in Marine Science, 2023)
The use of phytotherapy in aquaculture is rapidly increasing for more environmentally sustainable measures. The present work aimed to investigate the effects of different dietary levels of sweet basil, Ocimum basilicum, leaves ethanol (BEE) or aqueous (BAE) extracts (0, 200, 300, and 500 mg/kg) on Oreochromis niloticus growth, digestive enzyme activities, hemato-biochemical profile, antioxidant status, immune responses, and resistance against Streptococcus agalactiae. Oreochromis niloticus fingerlings (40.00 ± 1.00 g/fish, n = 210) were randomly divided into seven triplicated groups (control, BEE200, BEE300, BEE500, BAE200, BAE300, and BAE500) and fed the experimental diets for 8 weeks. The results revealed that dietary inclusion of BEE and BAE significantly improved final weight, weight gain, survival, and digestive enzyme activities. The growth response revealed a dose-dependent in favor of fish fed BEE. The hemato-biochemical biomarkers showed a significant improvement in RBCs, WBCs, hemoglobin, and lymphocyte, and a significant decrease in aminotransferases, creatinine, and cholesterol levels with dietary basil extracts. The cellular and humoral immune responses (phagocytic activity, phagocytic index, lysozyme activity, immunoglobulin) were significantly improved with increasing BEE and BAE in a dose-dependent manner. The expression of IL-1β and TNF-α genes were increased, while TGF-β was decreased in a dose-dependent manner and BEE500 have the highest expression. The antioxidant balance was improved with increasing basil extracts supplementation, and the BEE500 group showed the best antioxidant status. Dietary BEE and BAE increased Nile tilapia resistance to S. agalactiae. In conclusion, the dietary supplementation of both ethanolic and aqueous extracts could improve the growth performance and physiological, and immune-antioxidant status of Nile tilapia.